Aging Effect on Audiovisual Integrative Processing in Spatial Discrimination Task - Zou, Zhi; Chau, Bolton K. H.; Ting, Kin-Hung; Chan, Chetwyn C. H. (Frontiers in Aging Neuroscience, 2017)
Multisensory integration is an essential process that people employ daily, from conversing in social gatherings to navigating the nearby environment. The aim of this study was to investigate the impact of aging on modulating multisensory integrative processes using event-related potential, and the validity of the study was improved by including “noise” in the contrast conditions. Older and younger participants were involved in perceiving visual and/or auditory stimuli that contained spatial information. The participants responded by indicating the spatial direction (far versus near, and left versus right) conveyed in the stimuli using different wrist movements. Electroencephalograms were captured in each task trial, along with the accuracy and reaction time of the participants’ motor responses. Older participants showed a greater extent of behavioral improvements in the multisensory (as opposed to unisensory) condition compared to their younger counterparts. Older participants were found to have fronto-centrally distributed super-additive P2, which was not the case for the younger participants. The P2 amplitude difference between the multisensory condition and the sum of the unisensory conditions was found to correlate significantly with performance on spatial discrimination. The results indicated that the age-related effect modulated the integrative process in the perceptual and feedback stages, particularly the evaluation of auditory stimuli. Audiovisual integration may also serve a functional role during spatial-discrimination processes to compensate for the compromised attention function caused by aging.